Creación de la banda musical femenina de la Casa de la Cultura Ecuatoriana “Benjamín Carrión” núcleo de Los Ríos período 2015 - Castro Mindiola, Tomás Valentín (2015)
In Ecuador, and in the province of Los Rios lack of cultural identity originated long ago, has caused a number of problems of social and cultural nature, we need to identify what our, people, customs. Music is one of the most widespread and constant in the daily life of our society human activities, not only nourishes one of the industries that moves more money worldwide but accompanies the individual in every day of his life. In this sense we can say that hardly spend a day of our lives without listening to some music. We use it voluntarily, assiduously and systematically (radio, recordings, and concerts). We walked through the streets without noticing that the sound information our brain receives and processes, including large doses of foreign musical experience that they own, at least at first unconscious level. The soundscape that our society has generated and is present in all our activities, has music as one of the most characteristic components. Thus the fact musical projects beyond the specific times that the individual dedicates. Music, within the activities assumed by young people is the most popular because it is the language with which it is identified, it is expressed and / or communicates. Traditionally in the section of the Media Education, although the company has music as a constant companion and individual student lives it as well, a contradiction is generated because it does not match the experience of the linear discipline with the interests of young people. Musical Band Women's House of Culture Core Rivers is emerging as cross base curriculum for all students in schools in the city. The band intends to incorporate a range of possibilities that makes it a fun, educational and higher cognitive enhancer space operations. This band includes the need for an institutional space in which to channel the concerns of many young people who like, prefer and take it as a discipline. The band is conceived as an open and collective space that promotes the artistic and cultural development in which the DO, KNOW, AND BE combine to enhance the musical intelligence and aesthetic sensibility of the students as individuals and as members of a group. The province of Los Rios through the House of Ecuadorian Culture, in their quest to spread and strengthen our montubia and Ecuadorian music through instrumental, indigenous academic training of our people, improving day by day in the social and cultural sphere It proposes the creation of the women's Musical Band of the House of Culture Core of Los Rios, with the intention of offering the female youth population, disadvantaged province in access to the collective practice of classical music and oral tradition as a mechanism to contribute to the exercise of cultural rights of children and youth of Babahoyo and the province